Experimental investigation of the effect of ozone on auto-ignition behaviors of pyrolysis gas of kerosene - Zheng, Dong; Xiong, Peng-fei (Fuel (Guildford), 2021)
•Effect of ozone on auto-ignition behaviors of pyrolysis gas of kerosene.•Rapid compression machine experiments.•Ignition enhanced by additive ozone.•Active radicals and thermal effects in ozone assisted ignition. Additive ozone as a promising aiding can enhance ignition and combustion behaviors. In this study auto-ignition behaviors of pyrolysis gas of kerosene assisted by O3 are experimental investigated in a rapid compression machine. The ignition delay times of pyrolysis gas varying with additive O3 concentration from 0 to 1200 ppm have been measured at the conditions of TC = 877.7–917.2 K, PC = 3.3–4.4 MPa, φ = 1.0 and 0.5. The measured results show that with about 1195 ppm ozone the ignition delay time effectively decreases by a factor of about 5 at TC = 877.7 K, PC = 3.3 MPa and φ = 1.0. The ignition delay time exponentially decreases with the increasing of O3 concentration. Integrating the optimized USC-II mechanism with O3 sub-mechanism, the ignition delay times assisted by O3 are calculated at wider temperature regimes. The results demonstrate that the auto-ignition enhancement by O3 at low temperature regime is more significant as compared to the high temperature regime. Further analysis reveals that with O3 addition a peak of heat release appears at the initial time, leading to a temperature jump. Meanwhile the active species concentrations increase. At low temperature regime the temperature jump and active species concentrations increase considerably, so auto-ignition enhancement by O3 is more significant. Kinetic analysis found that the presence of O3 molecules rapidly activates the chain reaction paths O3 → O → HCO → HO2 → OH → H2O. During the chain reaction paths, vital radicals O, HCO, HO2 and OH are greatly generated, and a considerable amount of heat is released. By both active radicals and thermal effects, the auto-ignition of pyrolysis gas of kerosene has been enhanced.